Protective Effects of Selenopyran Against Carbon Tetrachloride Hepatotoxicity in Rats - L. B. ZAVODNIK; D. B. VOLOSHIN; A. SKOMOROSHKO; T. N. BUDKO1; V. I. KONDAKOV; R. N. LIAKH1; A. M. KHOKHA; B. PALECZ (International Journal of Secondary Metabolite)
Protective Effects of Selenopyran Against Carbon Tetrachloride Hepatotoxicity in Rats